Invitations to play: designing for family engagement through STEAM exhibits in community settings - Reimer, Paul N.; Moreno, Celeste (Frontiers in Computer Science, 2024)
Intergenerational play between children and their family members provides a rich context that can inform family-centered interaction design. Despite research on the roles and perspectives in adultchild interactions, less is known about the design elements and features of voluntary interaction settings that provide opportunities for family members to collaborate and play in joint, balanced ways. To this end, we report the qualitative results of our design and implementation of three interactive STEAM exhibits installed in an early childhood education center over a six-month period. Our findings surface insights and tensions related to the design features' impact on supporting family engagement in STEAM exhibits, emergent aspects of family-centered play, and supports needed to implement family-centered STEAM exhibits. Other designers, such as those who design with new technologies or explore human-computer interactions, can learn from our process of iteration and adjustment based on family interactions.